The anthelmintic efficacy of papaya latex in a rodent-nematode model is not dependent on fasting before treatment - Luoga W.; Mansur F.; Buttle D.J.; Duce I.R.; Garnett M.C.; Behnke J.M. (2024)
In earlier studies of the anthelmintic activity of plant cysteine proteinases (CPs), a period of food deprivation was routinely employed before administration of CPs, but there has been no systematic evaluation as to whether this does actually benefit the anthelmintic efficacy. Therefore, we assessed the effect of fasting on the efficacy of CPs from papaya latex (PL) against Heligmosomoides bakeri in C3H mice. We used a refined, supernatant extract of papaya latex (PLS) with known active enzyme content. The animals were divided into three groups (fasted prior to treatment with PLS, not fasted but treated with PLS and fasted but given only water). The study demonstrated clearly that although food deprivation had been routinely employed in much of the earlier work on CPs in mice infected with nematodes, fasting has no beneficial effect on the efficacy of PLS against H. bakeri infections. Administration of CPs to fed animals will also reduce the stress associated with fasting. 2011 Cambridge University Press.